From Bedside to Policy: The Nurse’s Role in Advancing Hospital Infection Control - OLWANI, JAWAHER MOHAMMED; AL-RUWAILI, NAWAL AL-FAHOU FLEIH; AL-RUWAILI, SUAD ALI AYED; OLWANI, ZAINAB MOHAMMED; AL-ZARE, LARA HAMED AWAD; ALSHAMMRI, ZUHUR MUZIL; ALENAZY, SARA AHMED; ALDEAN, SHARIFH ABDULLH; ALJEDAANI, RANA ABDULLAH; JWKHAB, HAMS IBRAHIM; et al. (Journal of Posthumanism, 2024)
The future of nursing in infection control lies in strengthening education, ensuring adequate resources, fostering leadership, integrating technology, and embracing global collaboration. By implementing these strategic recommendations, healthcare systems can support nurses in their indispensable role as frontline defenders against infection, securing safer environments for patients and communities worldwide